EFEKTIVITAS DAN DAMPAK PROGRAM BANTUAN KELOMPOK USAHA BERSAMA (KUBE) TERHADAP PENDAPATAN DAN KESEMPATAN KERJA RUMAH TANGGA SASARAN (RTS) DI KABUPATEN GIANYAR - Ningsih, Dewa Ayu Warta Putri; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
The purpose of this research is to analyze the effectiveness level of KUBE program in RTS in Gianyar regency, to analyze the presence or absence of Increased income and RTS employment opportunity after receiving KUBE assistance in Gianyar regency. The number of samples in the study were 77 respondents, the amount was determined based on Slovin approach with proportionate stratified random sampling method. The analytical technique used in this study is non-parametric statistic test different Wilcoxon. Effectiveness analysis results show that the success rate of KUBE assistance program is seen from the input, process and output indicators in Gianyar regency very effective. Similarly, Wilcoxon's analysis also shows that KUBE assistance programs have a significant positive impact or an increase in income and employment of Target Households in Gianyar Regency. It is recommended that the government keep running the KUBE-assisted program in order to provide the additional knowledge needed to increase revenue in line with the objective of KUBE program assistance. Keywords : Program effectiveness, KUBE, income, Job Opportunities